The option to expand a project: its assessment with the binomial options pricing model - Salvador Cruz Rambaud; Ana María Sánchez Pérez (Operations Research Perspectives, 2017)
Traditional methods of investment appraisal, like the Net Present Value, are not able to include the value of the operational flexibility of the project. In this paper, real options, and more specifically the option to expand, are assumed to be included in the project information in addition to the expected cash flows. Thus, to calculate the total value of the project, we are going to apply the methodology of the Net Present Value to the different scenarios derived from the existence of the real option to expand. Taking into account the analogy between real and financial options, the value of including an option to expand is explored by using the binomial options pricing model. In this way, estimating the value of the option to expand is a tool which facilitates the control of the uncertainty element implicit in the project.
Keywords: 330; Real options; Option to expand; Binomial options pricing model; Investment project appraisal